1992
DOI: 10.1111/j.1460-9568.1992.tb00160.x
|View full text |Cite
|
Sign up to set email alerts
|

The Somatotopic Organization Within the Cat's Thalamic Reticular Nucleus

Abstract: The organization of the somatosensory representation within the cat's thalamic reticular nucleus (TRN) was studied. Focal injections of horseradish peroxidase (HRP), wheatgerm agglutinin conjugated to HRP, and/or [3H]proline were made into somatosensory cortical areas 1 (S1) and 2 (S2). The resultant labelling in the thalamus was analysed. Single injections into S1 result in single zones of terminal labelling in TRN that are restricted to the centroventral part of the sheet-like nucleus. In reconstructions fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 38 publications
3
56
1
Order By: Relevance
“…No immunoreactivity was detected in the postsynaptic densities of symmetrical synapses made by GABAergic F type terminals mainly from the RTN in both species (Ohara et al, 1980;Montero and Scott, 1981; see reviews by Jones, 1985;Liu et al, 1995b) or by GABAergic PSD on other neuronal profiles. The presence of the receptor proteins at postsynaptic densities of glutamate containing asymmetrical synapses on RTN cells is also indicative of the presence of collateral thalamocortical and corticothalamic excitatory synapses on these cells (Jones, 1975;Yen et al, 1985;Crabtree, 1992). Ionotropic effects have been demonstrated physiologically on these cells (de Curtis et al, 1989), but to date NMDA receptor effects have not been shown.…”
Section: Distribution Of Glutamate Receptors In Neuronal Circuitry Ofmentioning
confidence: 94%
“…No immunoreactivity was detected in the postsynaptic densities of symmetrical synapses made by GABAergic F type terminals mainly from the RTN in both species (Ohara et al, 1980;Montero and Scott, 1981; see reviews by Jones, 1985;Liu et al, 1995b) or by GABAergic PSD on other neuronal profiles. The presence of the receptor proteins at postsynaptic densities of glutamate containing asymmetrical synapses on RTN cells is also indicative of the presence of collateral thalamocortical and corticothalamic excitatory synapses on these cells (Jones, 1975;Yen et al, 1985;Crabtree, 1992). Ionotropic effects have been demonstrated physiologically on these cells (de Curtis et al, 1989), but to date NMDA receptor effects have not been shown.…”
Section: Distribution Of Glutamate Receptors In Neuronal Circuitry Ofmentioning
confidence: 94%
“…Thus, the visual (Montero et al, 1977;Crabtree and Killackey, 1989;Conley and Diamond, 1990;Lozsá di et al, 1996) and somatosensory (Hoogland et al, 1987;Crabtree, 1992a,b) sectors receive mapped inputs from modality-related primary cortical areas. Furthermore, inputs from two or more modality-related cortical areas are largely segregated in the visual sector (Crabtree and Killackey, 1989;Conley and Diamond, 1990;Coleman and Mitrofanis, 1996;Lozsádi et al, 1996), whereas such inputs overlap in the somatosensory sector (Crabtree, 1992b).…”
Section: Indexing Terms: Auditory Thalamus; Slabs; Projections; Collamentioning
confidence: 98%
“…However, the projections of cells in this sector to the ventral subdivision of POm are not topographically organized even though most of these projections arise from the same cells that project to VB. A preliminary description of the data has been reported (Crabtree, 1994).…”
mentioning
confidence: 99%